2021
DOI: 10.1021/acs.jpcc.1c06534
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Transition on the Fractal Surface Developed by Size-Selected Ag Nanoclusters

Abstract: Surface morphology and wetting property of silver nanocluster-deposited films have been comprehensively investigated. A gas aggregation-type magnetron sputtering process is used to produce Ag nanoclusters, and the films are prepared by varying the cluster ion currents. The morphological result suggests that the deposited clusters agglomerate over the surface and also the overall size distribution is affected with increasing ion current. The morphological data are used to characterize various statistical parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…4g). 95 Yadav et al also found that the hydrophobicity increases with the increase in the fractal dimension, 96 and Volkmann et al experimentally and theoretically found that organic adsorption is related to the fractal dimension. 97…”
Section: Wetting Theorymentioning
confidence: 95%
See 1 more Smart Citation
“…4g). 95 Yadav et al also found that the hydrophobicity increases with the increase in the fractal dimension, 96 and Volkmann et al experimentally and theoretically found that organic adsorption is related to the fractal dimension. 97…”
Section: Wetting Theorymentioning
confidence: 95%
“…4g). 95 Yadav et al also found that the hydrophobicity increases with the increase in the fractal dimension, 96 and Volkmann et al experimentally and theoretically found that organic adsorption is related to the fractal dimension. 97 In addition, Wang et al summarized ve contact states of droplets on the microstructured surface based on classic wetting states and special wetting phenomena in nature: 98 the Wenzel state, the Cassie state, the 'Lotus' state with a high contact angle and low adhesion (Fig.…”
Section: Development Of Wenzel and Cassie Theoriesmentioning
confidence: 95%
“…More importantly, CBD effectively addresses the challenges associated with traditional wet chemical methods, providing a more advanced and precise approach to material synthesis for sensors. 32,[34][35][36] CBD excels at producing materials with high purity and controlled morphology, allowing the synthesis of NCs with tailored shapes and sizes, 37,38 essential for optimizing sensor performance. CBD is particularly suitable for constructing MOS-based gas-sensing materials modified with noble metals.…”
Section: Introductionmentioning
confidence: 99%